Linking on-ground practices with policies in livestock systems in eastern Africa - Thornton, Philip K. (International Livestock Research Institute, 2020)
The Program for Climate-Smart Livestock (PCSL) is exploring the future aspirations of smallholder farmers and the threats and opportunities they face as a result of climate change. These insights will inform program interventions as well as livestock-related policy processes.